2013
DOI: 10.4174/jkss.2013.84.4.231
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of preoperative serum levels of carbohydrate antigen 19-9 in colorectal cancer

Abstract: PurposeCarcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA 19-9) are the most frequently used tumor markers in the clinical setting of colorectal cancer (CRC). This study was designed to investigate the correlation between preoperative serum levels of CA 19-9 (pre-CA 19-9) and the clinicopathologic factors of patients with CRC.MethodsA study was performed on 333 patients with histologically diagnosed colorectal adenocarcinoma between December 2008 and November 2011, based on prospective collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 14 publications
(17 reference statements)
1
27
0
Order By: Relevance
“…It was also shown that an increase in CEA level implies a higher recurrence rate and worse prognosis (Wanebo et al, 1978). The overall reported incidences of high CA 19-9 levels in preoperative CRC patients range from 10.6 to 24.4% (Yu et al, 2013). In some previous studies, a high preoperative CA 19-9 level was shown to be independently associated with high pre-CEA, lymph node metastasis, large tumor size, and peritoneal seeding (Yang et al, 2004;Yu et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It was also shown that an increase in CEA level implies a higher recurrence rate and worse prognosis (Wanebo et al, 1978). The overall reported incidences of high CA 19-9 levels in preoperative CRC patients range from 10.6 to 24.4% (Yu et al, 2013). In some previous studies, a high preoperative CA 19-9 level was shown to be independently associated with high pre-CEA, lymph node metastasis, large tumor size, and peritoneal seeding (Yang et al, 2004;Yu et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…The overall reported incidences of high CA 19-9 levels in preoperative CRC patients range from 10.6 to 24.4% (Yu et al, 2013). In some previous studies, a high preoperative CA 19-9 level was shown to be independently associated with high pre-CEA, lymph node metastasis, large tumor size, and peritoneal seeding (Yang et al, 2004;Yu et al, 2013). However, the present data are insufficient to recommend CA 19-9 for staging, surveillance, or monitoring treatment of patients with CRC (Duffy et al, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…However, individual biomarker lacks sensitivity and specificity [13][14][15]. CEA and CA199 are the most frequently used tumor biomarkers in the clinical diagnosis of CRC but the AUC of CEA (AUC = 0.6995) and CA199 (AUC = 0.6518) are low [23,24]. Besides that, LP(a) (AUC = 0.6942) is superior to CA199 and it is a risk factor for atherosclerotic diseases such as coronary heart disease and stroke.…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown since the nineties that it is an independent prognostic factor [21] and is useful in metastatic disease [22]; recently its value has been demonstrated for follow-up [23]. Increased CA 19-9 has been correlated with high CEA, lymph node metastasis, right colon tumors, large tumor size and peritoneal seeding [24]. We have shown that CA 19-9 is more frequently increased in G3 tumors, independently of the (clinically established) stage.…”
Section: Discussionmentioning
confidence: 99%